2020
DOI: 10.5812/jjhs.100148
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Compassion-Focused Therapy (CFT) on Blood Cortisol and Cognitive-Emotion Regulation in Drug Abusers

Abstract: Objectives: This study aimed to investigate the efficacy of compassion-focused therapy on blood cortisol and cognitive-emotion regulation among drug abusers. Methods: It was a quasi-experimental study with a pretest-posttest design and a control group. The statistical population consisted of all men with drug abuse referring to Torbat-e-Heydariyeh Adult Drug Abuse Clinic in 2018, 40 of whom were selected by simple random sampling for the experimental and control groups. The experimental group was trained for 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Ghodrati Torbati et al . [ 30 ] examined the effects of CFT on blood cortisol and cognitive-emotional regulation in drug users and showed that the compassion-focused behavioral therapy had a significant effect on blood cortisol and emotion regulation in post-test. Izanloo et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ghodrati Torbati et al . [ 30 ] examined the effects of CFT on blood cortisol and cognitive-emotional regulation in drug users and showed that the compassion-focused behavioral therapy had a significant effect on blood cortisol and emotion regulation in post-test. Izanloo et al .…”
Section: Discussionmentioning
confidence: 99%
“…The sample consisted of 30 patients (15 in each group) based on statistical formula 1 and similar studies. [ 29 30 ] Sampling method of this project was available and in the next step, simple random sampling was used to assign people to two experimental and control groups [ Figure 1 ]. The sampling method of this project was available and based on inclusion and exclusion criteria as random appointment in experimental and control groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, researchers have theoretically and empirically confirmed the prominent role of cognitive emotion regulation in the pathology of emotional and addictive disorders (16). Emotional dysregulation is a set of conscious and unconscious strategies manifested as the inability to control and moderate emotional expression and causes incorrect re-appraisal of cognitive changes before the occurrence of emotion (17,18).…”
Section: Introductionmentioning
confidence: 99%